Regulation of PPARγ coactivator 1α (PGC-1α) signaling by an estrogen-related receptor α (ERRα) ligand - Willy, Patricia J. (National Academy of Sciences, 2004)
Peroxisome proliferator-activated receptor γ (PPARγ) coactivator 1α (PGC-1α) is a transcriptional coactivator that is a key component in the regulation of energy production and utilization in metabolic tissues. Recent work has identified PGC-1α as a strong coactivator of the orphan nuclear receptor estrogen-related receptor α (ERRα), implicating ERRα as a potential mediator of PGC-1α action. To understand the role of ERRα in PGC-1α signaling, a parallel approach of high-throughput screening and gene-expression analysis was used to identify ERRα small-molecule regulators and target genes. We report here the identification of a potent and selective ERRα inverse agonist that interferes effectively with PGC-1α/ERRα-dependent signaling. This inverse agonist inhibits the constitutive activity of ERRα in both biochemical and cell-based assays. Also, we demonstrate that monoamine oxidase B is an ERRα target gene whose expression is regulated by PGC-1α and ERRα and inhibited by the ERRα inverse agonist. The discovery of potent and selective ERRα modulators and their effect on PGC-1α signaling provides mechanistic insight into gene regulation by PGC-1α. These findings validate ERRα as a promising therapeutic target in the treatment of metabolic disorders, including diabetes and obesity.